Brexit vote and its implications on Market Access' internationalization strategy - Tereza Krátká (2017)
This report is the product of the 6-month curricular internship at Market Access, a Portuguese international business consultancy firm. Market Access is successful in the national market and as a form of international expansion, in 2015 a strategic partnership with UK-based Cormack Consultancy Group started. In June 2016, the unexpected result of the Brexit referendum in the UK brought concerns regarding this partnership.The report aims to offer strategy recommendations for Market Access regarding its Scottish-based partner Cormack Consultancy Group given the recent events. The question of Brexit is discussed with the use of testimonials of leading European economists, government institutions, and official statements of UK and EU representatives. Three scenarios of post-Brexit UK-EU trade relations are described, and analysed in macroeconomic perspective and in the view of Market Access - Cormack Consultancy Group partnership. As the partnership is not fully developed and established, and both firms are young, growing, and flexible, the general medium term strategy recommendation for Market Access is to remain flexible and be ready to adapt their services. A strategy applicable for the period before the conclusion of Brexit negotiations is suggested, and so are recommendations specific for each scenario following Brexit. This report clarifies some of the uncertainties that arose as a result of the Brexit vote and offers strategy guidance to Market Access that is based on structured and systematic analysis.